Ensuring Quality of Educational Preparation of the Future Managers of Education - Viktor Bereka (Pedagogical Discourse, 2014)
The article deals with the theoretical and methodological approaches to the consideration of assessment problem of training quality of future managers of education. The main components of specified process such as the determination of conceptual principles, the development of standardization model, the modeling of professional education quality, and the definition of the conceptual and methodological principles of quality system projecting have been described. The study of the introduction of credit-modular system of educational process, the basic regularities and requirements to the skills of holders of masters’ degree has been carried out by the author. The analysis of scientific literature and the results of the survey made it possible to identify the components of the Quality Assurance Masters Training of future managers of education: the actuality of introducing of training programs in accordance with the State Standard of Managers Training, the use of modern technologies and methods of the organization of educational process, the qualitative methodological material and technical provision, the availability of effective system of educational monitoring, the matching of training system of future managers of education to the requirements of global educational society, the providing managers with the higher range of opportunities of choosing of studying forms and academic reporting, the orientation of training programs of future managers of education on their personal and professional development. In the article the prospects of appointed issue learning have been defined.